UJI AKTIVITAS ANTIOKSIDAN INFUSA DAUN KELOR (Moringa oleifera, Lamk) DENGAN METODE 1,1- diphenyl-2-picrylhydrazyl (DPPH) - NI NYOMAN YULIANI; DESMIRA PRIMANTY DIENINA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2015)
Free radicals are known to mediate a variety of diseases. Some plants such as the chemical content of phenolic compounds and flavonoids have been reported to correlate to the activity of free radical scavenging. One of the plants that have the potential as a catcher of free radicals is moringa (Moringa oleifera, Lamk). This research is to test the antioxidant activity and how much the activity of antioxidants found in Moringa leaves infuse spectrophotometry with DPPH. Moringa leaves infuse made in various concentrations. Absorbance measurements carried out at a wavelength of 517.6 nm todetermine the% reduction of free radicals, followed by calculating the IC50 value. The results showed that infuse the leaves of Moringa (Moringa oleifera, Lamk) has a very weak antioxidant activity with an IC50 value of 2151.33 ppm.